The Future of Hospitality : Leveraging Robotics for Enhanced Customer Service - Somchai Wijit; Somsak Chaisongkram; Prayut Chan-o-cha (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This paper explores the growing adoption of robotics in the hospitality sector to deliver innovative customer service. Robots are increasingly employed for check-ins, concierge services, and room delivery, offering consistency and efficiency. The study evaluates customer satisfaction and cost implications, as well as ethical considerations for workforce displacement.